Information Pollution in Iraqi Journalism…Study in Causes and Sources - A research drawn from a Master Degree thesis - Al-Salim , Hamdan Kidr; Saaed Aswad, Hind (ALBAHITH ALALAMI, 2025)
Information pollution is regarded as a big problem facing journalists working in the editing section, whereby journalistic materials face such pollution through their way across the editing pyramid. This research is an attempt to define the concept of journalistic information pollution, and what are the causes and sources of this pollution. The research applied the descriptive research method to achieve its objectives. A questionnaire was used to collect data. The findings indicate that journalists are aware of the existence of information pollution in journalism, and this pollution has its causes and resources.